Restauri e musei Il paesaggio culturale dei lungarni di Pisa dal secondo dopoguerra a oggi - Giusti, Francesca (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2023)
The gaze of the Grand Tour travellers on the Lungarni of Pisa, in the background of the nineteenth-century process of transformation of the banks and buildings that surround it, helping to define its cultural vocation. The turning point coincided with the second post-war period and began with the conversion of the former convent of San Matteo into a national museum, designed by Piero Sanpaolesi. The project is part of the international debate on culture and museum practice, offering important topics for reflection on the relationship between restoration and musealization, museums, city and recovery of river banks. With the theory of museums in diachronic continuity and contiguity of path (Palazzo Reale, Palazzo Lanfranchi, Palazzo Blu, Navi di Pisa and science), the concept of 'system' takes shape, as a set of multiple museums, between them different, but united by the link with the territory that welcomes them, represented by the Arno that crosses the city and its history.